Stoicism and its Influence in the Culture of New Testament Theology & Paul's Writings - Saputra, Felicia Celine; Rumondor, Imanuela Kimberly (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2025)
This paper examines the interplay between Stoic philosophy and early New Testament theology, with a particular focus on Pauline writings. It explores how core Stoic concepts—such as logos, virtue, and natural law—were strategically adapted by early Christian thinkers to communicate the gospel within a Hellenistic intellectual framework. The discussion reveals three key points of theological tension: 1) Resurrection versus Immortality of the Soul: Whereas Stoicism posits that the soul merely returns to the universal order, Christian doctrine asserts the resurrection of the body and the promise of eternal, transformed identity (Engberg-Pedersen, 2020; Ferguson, 2021). 2) Personal God versus Pantheistic Logos: The Stoic view of an impersonal, all-pervading logos contrasts sharply with the Christian emphasis on a personal, relational God who actively engages with creation (Arnold, 1971; Wilson, 2023). 3) Grace versus Self-Sufficiency: Although Stoic ethics valorize self-sufficiency achieved through reason and discipline, Paul redefines these ideals by grounding moral strength in divine grace, thereby highlighting human dependence on Christ (Malherbe, 2022). This research shows how early Christian theology both borrowed from and diverged from prevailing philosophical traditions, thus laying the groundwork for a distinctive doctrinal identity. This synthesis not only facilitated the spread of Christianity among a philosophically sophisticated audience but also continues to offer a rich framework for contemporary theological dialogue and interfaith engagement. It is expected that further exploration of this convergence will deepen our understanding of the dynamic relationship between secular philosophy and religious thought, with implications for modern ethical discourse and apologetics.